从多模态话语分析视角分析文化负载词的字幕英译：以综艺节目《青春环游记3》为例 = Subtitle translation of Culture-loaded Words from the perspective of multimodal discourse analysis: a case study of Youth Periplous 3 - 戴筠懿 Teh, Yun Yi (Nanyang Technological University, 2022)
近年来，多模态话语分析成为了影视翻译研究的新方向。虽然多模态话语分析确立了多模态关系之间的重要性，但在目前的研究中，很少有人将多模态关系与翻译策略结合做分析，以多模态视角来分析综艺节目字幕翻译的研究也仍有不足。 因此，本文以综艺节目《青春环游记3》中的文化负载词英译字幕为研究对象，运用张德禄的多模态话语分析综合框架探讨节目中多模态与字幕的具体关系，并以Aixelá的文化负载词翻译策略分析字幕的翻译策略，旨在发现其中规律，提出问题。 研究发现，节目的多模态关系有互补强化（突出、主次、扩充），互补非强化（交叉、协调），以及非互补关系（交叠、内包、语境交互）。在互补关系中，其他模态起到辅助作用，与文字共同表现意义。因此，使用文化保留类的翻译策略，可达到文化传播的作用。在翻译非互补关系的文化负载词时，选择文化替换类的翻译策略则能让观众在短时间内理解并接受输出的内容，保证交际效果。 该研究突破了传统字幕翻译的局限性，将图像和文字外的模态，如人物动作和音乐一同列入研究，探讨了综艺节目中多模态之间的关系及它们对字幕翻译策略的影响，也提出看法，希望能尽微薄之力，为综艺节目的字幕翻译提供一点启发。 In recent years, multimodal discourse analysis has become a new approach in audiovisual translation studies. Although multimodal discourse analysis has established the importance of multimodal relations, studies combining multimodal relations with translation strategies are scarce. The research on subtitle translation of variety shows is also lacking. Therefore, this paper aims to identify specific multimodal relations present in the Chinese variety show Youth Periplous 3 using Zhang Delu’s Synthetic Theoretical Framework for Multimodal Discourse Analysis, then analyses the subtitle translation strategies used in translating culture-loaded words according to Aixelá's model of translating culture-specific items, in hopes to discover patterns and implications. The research reveals that multimodal relations in the variety show includes complementary reinforcement relationship (highlighting, primary and secondary, extension), complementary non-reinforcement relationship (intersection, coordination), and non-complementary relationship (overlap, inclusion and contextual interaction). In the complementary relationship, modes other than words play an auxiliary role in expressing meaning of the culture-loaded word. Hence, the use of cultural conservation translation strategies can achieve the goal of cultural transmission. Meanwhile, translating culture-loaded words in non-complementary relationship with cultural substitution translation strategies brings across message in a way that audience of different cultures can understand. This study breaks through the limitations of traditional subtitle translation research, and includes modes other than images and words, such as actions and music. It states the different multimodal relations in the variety show, explores the effect of multimodal relations on subtitle translation strategies, with the intention to provide guidance for future translators of variety shows and improve the quality of subtitle translation.